Matricellular protein SPARC/osteonectin expression is regulated by DNA methylation in its core promoter region. Issue 5 (31st March 2015) - Torres‐Núñez, Eva; Cal, Laura; Suárez‐Bregua, Paula; Gómez‐Marin, Carlos; Moran, Paloma; Gómez‐Skarmeta, Jose Luis; Rotllant, Josep
<x xml:space="preserve">Abstract</x> Background: SPARC/osteonectin is an evolutionarily conserved matricellular protein that modulates cell–matrix interaction and cell function. In all vertebrates, SPARC is dynamically expressed during embryogenesis. However, the precise function of SPARC and the regulatory elements required for its expression in particular during early embryogenesis are largely unknown. Results: The present study was undertaken to explore the molecular mechanisms that regulate sparc gene expression by in vivo functional characterization of the sparc promoter and identification of possible putative regulatory elements that govern basal promoter activity. We report here transient expression analyses of eGFP expression from transgenic zebrafish containing a Sparc‐iTol2‐eGFP‐BAC and/or 7.25 kb‐sparc‐Tol2‐eGFP constructs. eGFP expression was specifically found in the notochord, otic vesicle, fin fold, intermediate cell mass, and olfactory placode of BAC and Tol2 transposon vectors injected embryos. Deletion analysis revealed that promoter activity resides in the unique 5′‐untranslated intronic region. Computer‐based analysis revealed a putative CpG island immediately proximal to the translation start site within the intron sequence. Global inhibition of methylation with 5‐Aza‐2‐deoxycytidine promoted sparc expression in association with decreasing CpG methylation. Conclusions: Taken together, these data identify a contributory role for DNA methylation in regulating sparc expression in zebrafish embryogenesis. Developmental Dynamics 244:693–702, 2015. © 2015 Wiley Periodicals, Inc.